PERENCANAAN PROGRAM INTERPRETASI WISATA ALAM BERBASIS KONSERVASI MANGROVE DI TAMAN WISATA ALAM MANGROVE ANGKE KAPUK JAKARTA - Lenny Yusrini; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2019)
One of the efforts to develop tourists’ understanding in maintaining sustainability at the natural tourist attractions is through nature conservation education. It can be achieved in the form of nature tourism interpretation program. This study aims to create and develop an interpretation planning program for visitors based on mangrove conservation to support sustainability of the Taman Wisata Alam (TWA) Mangrove Angke Kapuk Jakarta. TWA Mangrove Angke Kapuk Jakarta as one of the nature attractions does not have and has not developed an interpretation program for visitors. This study is a descriptive qualitative study using interview and observation methods to collect data based on Sharpe’s (1982) interpretation planning analysis. The result is the interpretation planning,they are: (1) the objects, themes, and interpretation materials; (2) the purpose and target of interpretation; (3) interpretation program; (4) interpretation techniques; and (5) facilities development planning.